Engineered lentiviral vector targeting astrocytes In vivo - Colin, Angélique; Faideau, Mathilde; Dufour, Noelle; Auregan, Gwennaelle; Hassig, Raymonde; Andrieu, Thibault; Brouillet, Emmanuel; Hantraye, Philippe; Bonvento, Gilles; Déglon, Nicole (Glia, 2009)
Astrocytes are involved in key physiological brain processes, such as glutamatergic transmission and energy metabolism, often altered in neurodegenerative diseases. Targeted gene expression in astrocytes is needed to assess the contribution of these cells to physiological processes and for the development of new therapeutic strategies. However, most of the viral vectors currently used for gene transfer in the central nervous system (CNS) are highly neurotropic. We used mokola pseudotyping to shift the tropism of lentiviral vectors toward astrocytes and a detargeting strategy with miRNA to eliminate residual expression in neuronal cells. In primary cultures, we showed that incorporating target sequences for the neuron‐specific miR124 effectively abolished transgene expression in neurons post‐transcriptionally. Targeted expression of the LacZ reporter gene in astrocytes was achieved in the hippocampus, striatum, and cerebellum of the adult mouse in vivo. As a proof‐of‐principle, this new lentiviral vector was used to either overexpress or downregulate (RNA interference) the glial glutamate transporter GLAST into striatal astrocytes in vivo. These vectors provide new opportunities for cell type‐specific gene transfer in the CNS. © 2008 Wiley‐Liss, Inc.